Valuing Risk in the Workplace: Market Price, Willingness to Pay, and the Optimal Provision of Safety - Herzog, Henry W.; Schlottmann, Alan M. (The Review of Economics and Statistics, 1990)
Henry W. Herzog, Jr., Alan M. Schlottmann, Valuing Risk in the Workplace: Market Price, Willingness to Pay, and the Optimal Provision of Safety, The Review of Economics and Statistics, Vol. 72, No. 3 (Aug., 1990), pp. 463-470